2019
DOI: 10.1590/1807-1929/agriambi.v23n12p907-913
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiology of maize under water salinity and nitrogen fertilization in two soils

Abstract: The nitrogen fertilization, in general, minimizes the effects of salinity on plants, but the mitigating action depends on plant species, cultivar, soil texture and plant age, among other factors. The objective of this study was to evaluate the effects of irrigation water salinity and nitrogen fertilization on maize physiology and growth (Zea mays) in soils with different textures. The experiment was carried out in a greenhouse in Fortaleza City, CE, Brazil, in PVC soil columns (100 x 20 cm). The design was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…According to Figure 5A, the high-salinity water negatively affected the ear length, obtaining lower mean values (9.18 cm) than the low-salinity water (10.05 cm), with a reduction of 8.56%. This effect can be explained by the fact that salinity inhibits plant growth due to osmotic, toxic effects affecting absorption of essential nutrients and, consequently, yield components (Braz et al, 2019;Rodrigues et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure 5A, the high-salinity water negatively affected the ear length, obtaining lower mean values (9.18 cm) than the low-salinity water (10.05 cm), with a reduction of 8.56%. This effect can be explained by the fact that salinity inhibits plant growth due to osmotic, toxic effects affecting absorption of essential nutrients and, consequently, yield components (Braz et al, 2019;Rodrigues et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that there was no restriction in A in the substomatal chamber (Figure 1C), this reduction in A may be related to nonstomatal factors, such as accumulation of Na + ions and/or Clin the chloroplasts, which causes alterations in the state of the thylakoid membranes of chloroplasts that. These alterations, in turn, induce changes in the biochemical and photochemical processes involved in photosynthesis (Braz et al, 2019), causing the CO 2 available for photosynthesis not to be synthesized during the carboxylation phase (Morais et al, 2018). The results found in this study corroborate Lima, Fernandes, Soares, Gheiy and Fernandes (2020), who observed an increase in Ci and a reduction in A with the increase in irrigation water salinity from 0.3 to 3.5 dS m -1 , in passion fruit plants.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of salinization on plants is an extremely complex phenomenon that involves morphological (Targino et al, 2017;Braz et al, 2019), physiological (Lira et al, 2018) and biochemical (Simões et al, 2019) changes caused by low water availability to plants and by the toxicity of specific ions, reducing growth, development and yield of the crop.…”
Section: Introductionmentioning
confidence: 99%